OP59 #Have e-cigarettes re-normalized or displaced youth smoking?: a segmented regression analysis of repeated cross sectional survey data in england, scotland and wales. (September 2018) - Hallingberg, B; Maynard, O; Gray, L; MacKintosh, A; Lowthian, E; Moore, G
Abstract : Background: Small yet significant impacts of e-cigarettes on population smoking cessations rates indicate promise for harm reduction. However, non-smoking young people are increasingly experimenting with e-cigarettes, and while regular use remains rare, arguments for regulation have been driven by fears that e-cigarettes re-normalize smoking. Others counter that e-cigarettes may displace youth smoking and further de-normalize it. This study tests whether the secular decline in youth smoking prevalence, as well as perceived smoking norms, slowed or accelerated during the period from 2011–2015 (when e-cigarettes were emerging but prior to recent moves to regulate their use). Methods: Data were taken from the Smoking Drinking and Drug Use survey in England, Health Behaviour in School Aged Children/School Health Research Network surveys in Wales, and the Scottish Adolescents Lifestyle and Substance Use Surveys between 1998 and 2015, including 247, 515 13 and 15 year-old respondents. Segmented regression analyses examined trends for smoking prevalence (ever smoking and weekly smoking) and perceived smoking norms, testing for change in trend from 2011–15. Falsifiability checks examined change in trends for alcohol use and cannabis use for the same period. Results: In final models for the whole sample, there was no change in rate of decline for ever smoking (OR=1.01; CI 0.99 to 1.03), with a marginally significant slowing in the rate of decline for weekly smoking (OR=1.04; CI 1.00 to 1.08). This slowing decline in weekly smoking was however limited to groups for whom rates were declining prior to 2010 at a rate which could not be sustained (i.e. girls and 13 year olds), and occurred in a greater magnitude for other substances, including cannabis use (OR=1.21, CI 1.18 to 1.25) and alcohol use (OR=1.17; CI 1.14 to 1.19). There was consistent evidence across all subgroups of an increased rate of decline in the percentage of young people saying that smoking is ok (OR=0.83; CI 0.81 to 0.86). Conclusion: We found no evidence that the growing prevalence of e-cigarette use has led to increased experimentation with smoking, and some evidence that young people's perceptions against smoking as a normative behavior have hardened rather than softened. Although the decline in weekly smoking rates is slowing, this appears to reflect a floor effect and is of smaller magnitude than change in trend for other substances. While the idea that e-cigarettes renormalize smoking has been central to much policy debate surrounding regulation, these findings indicate no reason to believe that this renormalization is occurring.